IMPLEMENTASI PROGRAM TAKHOSSUS LPBA DI PONDOK PESANTREN RAUDLATUL MALIKIYAH - Agustin, Sylvia; Agustin, Maulid (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
The implementation of the Takhossus LPBA program at the Raudlatul Malikiyah Islamic Boarding School involves developing the Arabic language, teaching Arabic grammar rules, and implementing routine language activities. This program develops students' Arabic language skills, such as speaking, debating, hosting and delivering speeches. In addition, this research explains the history and teaching system of the program, and highlights the importance of nahwu and sharaf in learning Arabic to understand the structure and use of the language. The research methodology used is work analysis using primary and secondary data sources. The LPBA program in Islamic boarding schools is implemented through BANOM dirofiyah activities, which include routine Arabic language rules and sanctions for violators. This research aims to explore the implementation of the LPBA program in Islamic boarding schools using qualitative research methods. LPBA as a foreign language development institution encourages its members to speak Arabic every day to improve their language skills. Apart from that, Islamic boarding schools also implement the Takhassus LPBA program to deepen their knowledge of the Arabic language. Although the program faces challenges such as lack of student motivation resources, limited number of teachers, limited expertise, limited textbooks, teaching materials and multimedia resources, strategic steps have been taken to overcome these problems. Program evaluations are carried out periodically to ensure the effectiveness of activities. Keywords:  Takhossus; Arabic; Banom.